2021
DOI: 10.1002/mnfr.202100416
|View full text |Cite
|
Sign up to set email alerts
|

Acid Hydrolysis of Gluten Enhances the Skin Sensitizing Potential and Drives Diversification of IgE Reactivity to Unmodified Gluten Proteins

Abstract: Scope: Personal care products containing hydrolyzed gluten have been linked to spontaneous sensitization through the skin, however the impact of the hydrolysate characteristics on the sensitizing capacity is generally unknown. Methods and Results: The physicochemical properties of five different wheat-derived gluten products (one unmodified, one enzyme hydrolyzed, and three acid hydrolyzed) are investigated, and the skin sensitizing capacity is determined in allergy-prone Brown Norway rats. Acid hydrolyzed glu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(14 citation statements)
references
References 50 publications
1
13
0
Order By: Relevance
“…This phenomenon warrants further investigation, including the study of other allergens, the amount of allergen required to sensitize via the skin, the kinetics of IgE levels following oral exposure, and the underlying mechanisms. Of note, we have previously observed at clear dose–response in sensitization to gluten‐derived products (5–500 μg), and our results indicated that a 100‐fold reduction in the dose (5 μg) of E Glu could lead to sensitization when applied to the skin 15 …”
Section: Discussionsupporting
confidence: 62%
See 4 more Smart Citations
“…This phenomenon warrants further investigation, including the study of other allergens, the amount of allergen required to sensitize via the skin, the kinetics of IgE levels following oral exposure, and the underlying mechanisms. Of note, we have previously observed at clear dose–response in sensitization to gluten‐derived products (5–500 μg), and our results indicated that a 100‐fold reduction in the dose (5 μg) of E Glu could lead to sensitization when applied to the skin 15 …”
Section: Discussionsupporting
confidence: 62%
“…Skin‐mediated sensitization to the gluten‐derived hydrolysates induced limited IgE cross‐reactivity to Un Glu in wheat‐naïve rats before oral exposure to Un Glu. This is surprising, because we previously found, that all the hydrolyzed products retained the native antigenic epitopes present in Un Glu 15 . Indeed, Un Glu‐specific IgG1 levels were comparable to the product‐specific IgG1 levels, indicating that the immune system is exposed to Un Glu epitopes.…”
Section: Discussionmentioning
confidence: 77%
See 3 more Smart Citations